Fostering Students’ Environmental Care Characters Through Local Wisdom-Based Teaching Materials - Asrial, Asrial; Syahrial, Syahrial; Maison, Maison; Kurniawan, Dwi Agus; Putri, Embarianiyati (JPI (Jurnal Pendidikan Indonesia), 2021)
This study aims to describe teaching materials based on local wisdom in fostering a character of environmental care in students. Local wisdom can be interpreted as a local culture that guides life. The problem in this study refers to the teaching materials used by teachers based on local wisdom in fostering character in students. The method used for this research is qualitative by using observation, interview, and documentation techniques. The results of the analysis of teaching material needs based on local wisdom are analyzing teaching materials for class V SD which includes aspects of mapping Core Competencies and Basic Competencies. In conclusion, analyzing the need for local wisdom-based teaching materials, such as teaching materials that have a variety of materials that can be integrated with local wisdom, can activate students in learning, the need to develop teaching materials based on local wisdom.